Detection of interactions between the pea root rot pathogens Aphanomyces euteiches and Fusarium spp. using a multiplex qPCR assay. (19th July 2018) - Willsey, T. L.; Chatterton, S.; Heynen, M.; Erickson, A.
Abstract : Pea root rot complex (PRRC) describes a group of closely associated soilborne pathogens that cause root rot disease in field pea. Aphanomyces euteiches and several Fusarium spp. are the most prevalent and damaging microorganisms within this complex, although the impact of interspecific interactions on disease progression remains largely unexplored. Furthermore, a fast and reliable method of detecting and quantifying these pathogens is not currently available. The objectives of this experiment were to: (i) investigate the effect of microbial interactions on root rot severity in pea under greenhouse conditions; and (ii) characterize changes in colonization rates when multiple pathogens are present using qPCR. Seeds were exposed to three species of Fusarium and were planted into A. euteiches ‐infested soil in varying combinations. For each experimental treatment, an index of disease severity was used to visually rate disease symptoms. Additionally, two triplex quantitative PCR (qPCR) assays were designed to detect and quantify changes in pathogen population dynamics on the roots. Both assays demonstrated a high degree of sensitivity and efficiency. Results from two independent greenhouse trials indicated an increase in disease severity in the presence of multiple pathogen species compared to single inoculations. Specifically, roots infected with A. euteiches were more susceptible to fusarium root rot than those exposed only to Fusarium spp. These observations were confirmed by qPCR results, which revealed significant changes in colonization rates when multiple species were present. These findings suggest an increased risk of yield loss in regions where A. euteiches and Fusarium spp. co‐occur.